Accelerating Halal Logistics Certification in Indonesia: A System Dynamics Approach - Wynd Rizaldy; Prasadja Ricardianto; Sita Aniisah Sholihah; Bagus Sumargo (Dinasti International Journal of Education Management and Social Science, 2026)
This study investigates how halal logistics certification in Indonesia can be accelerated using a system dynamics approach to sustainable logistics governance. Certification is conceptualized as a dynamic governance system rather than a static compliance process, addressing persistent challenges such as long lead times, high costs, limited auditor capacity, and uneven service quality. Service quality dimensions of Halal Inspection Body  (LPH)   were first assessed using SERVQUAL across 77 halal-certified logistics companies, while their relative importance was determined through the Analytic Hierarchy Process (AHP) based on expert judgments. These weighted indicators were then integrated into a system dynamics model, supported by a review of 32 peer-reviewed studies, to simulate policy intervention scenarios. Simulation results indicate that coordinated improvements in auditor capacity, service quality, digitalization, and regulatory coordination primarily drive certification acceleration. Integrated policy-mix interventions generate non-linear performance gains, significantly improve certification lead-time rates and cost rates, while enhancing system stability and stakeholder satisfaction. The study provides policy-relevant insights for regulators and logistics service providers to strengthen sustainable halal logistics governance in Indonesia.